THE EXPERIENCE OF COMBATING THE SHADOW ECONOMY IN THE EUROPEAN COUNTRIES - E. Hakopyan (Вестник университета)
The economic crisis gave a powerful impulse to the European governments to fight against the shadow economy. Some European countries have developed and presented national strategies for combating the shadow economy. In fact, one of the most effective measures taken to reduce the size of the shadow economy is indirect measurement. In the first place among them is the modernization of the tax and social security systems. Long-term initiatives in the field of creating «e-government», in particular electronic payments in the public sector are one of the most important elements in changing the «old habits» of using cash.